2022
DOI: 10.3389/fnut.2022.859292
|View full text |Cite
|
Sign up to set email alerts
|

Liver Protein Expression in NASH Mice on a High-Fat Diet: Response to Multi-Mineral Intervention

Abstract: Male MS-NASH mice were maintained on a high-fat diet for 16 weeks with and without red algae-derived minerals. Obeticholic acid (OCA) was used as a comparator in the same strain and diet. C57BL/6 mice maintained on a standard (low-fat) rodent chow diet were used as a control. At the end of the in-life portion of the study, body weight, liver weight, liver enzyme levels and liver histology were assessed. Samples obtained from individual livers were subjected to Tandem Mass Tag labeling / mass spectroscopy for p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In such circumstances, hepatotoxicity is avoided through alternative metabolomics pathway. This pathway synthesize glutamine through glutamate while utilizing the ammonia (Soontornniyomkij et al, 2016;Varani et al, 2022). Increased liver glutamine and glutamate levels in both male and female HFD groups resonates the effect of chronic HFD feeding on liver detoxi cation capacity and adaptation to the alternative glutamine synthesis (Ruiz et al, 1991).…”
Section: Discussionmentioning
confidence: 95%
“…In such circumstances, hepatotoxicity is avoided through alternative metabolomics pathway. This pathway synthesize glutamine through glutamate while utilizing the ammonia (Soontornniyomkij et al, 2016;Varani et al, 2022). Increased liver glutamine and glutamate levels in both male and female HFD groups resonates the effect of chronic HFD feeding on liver detoxi cation capacity and adaptation to the alternative glutamine synthesis (Ruiz et al, 1991).…”
Section: Discussionmentioning
confidence: 95%
“…In one past study, Aquamin ® was reported to reduce symptoms of colitis in the 25-week IL-10−/− mouse model ( Aviello et al, 2014 ). Our own 16-week study demonstrated reduced liver inflammation in NASH mice on a high-fat diet ( Varani et al, 2022 ) while long-term (15–18 months) studies with healthy C57BL6 mice on a high-fat diet demonstrated reduced inflammation throughout the gastrointestinal tract, in the liver and systemically when Aquamin ® was incorporated into the diet ( Aslam et al, 2010 ; Aslam et al, 2012 ). While all of these past murine studies point to a direct anti-inflammatory effect, the findings are also consistent with an improved colonic barrier being the primary target of the intervention with anti-inflammation being a consequent of the improved barrier.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of Aquamin treatment was tested in a murine model of NAFLD. Groups of mice were fed a high-fat diet with fructose added to the drinking water with and without the addition of Aquamin for a period of 16 weeks [ 235 ]. They proved that Aquamin, which is rich in calcium, magnesium, and other elements (derived from red algae), prevents and can even help stop the progression of NAFLD ( Table 2 ).…”
Section: Aquaminmentioning
confidence: 99%